2015
DOI: 10.1002/14651858.cd001401.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Chest physiotherapy compared to no chest physiotherapy for cystic fibrosis

Abstract: Editorial group: Cochrane Cystic Fibrosis and Genetic Disorders GroupPublication status and date: New search for studies and content updated (no change to conclusions), published in Issue 12, 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 128 publications
1
52
2
6
Order By: Relevance
“…As manobras clássicas são drenagem postural, vibração e percussão (CASTAÑOS & RENTERÍA, 2008). Outras alternativas mais recentes incluem, técnica de expiração forçada (TEF), técnica do ciclo ativo da respiração (CAR), pressão expiratória positiva (PEP) e drenagem autógena (WARNOCK & GATES, 2015 …”
Section: Técnicas De Fisioterapia Respiratóriaunclassified
See 2 more Smart Citations
“…As manobras clássicas são drenagem postural, vibração e percussão (CASTAÑOS & RENTERÍA, 2008). Outras alternativas mais recentes incluem, técnica de expiração forçada (TEF), técnica do ciclo ativo da respiração (CAR), pressão expiratória positiva (PEP) e drenagem autógena (WARNOCK & GATES, 2015 …”
Section: Técnicas De Fisioterapia Respiratóriaunclassified
“…A técnica de expiração tem sido bastante eficaz na higiene brônquica de pacientes que tendem a ter o colapso das vias aéreas durante a tosse normal, como é o caso dos pacientes com fibrose cística. A TEF associada a drenagem postural mostrou-se bastante eficaz para o aumento da quantidade de secreção expectorada e no aumento da função pulmonar, gerando um aumento considerável na VEF1 e na capacidade funcional forçada (GOMIDE et al, 2007;WARNOCK & GATES, 2015).…”
Section: Técnica De Expiração Forçada (Tef)unclassified
See 1 more Smart Citation
“…The effect of physiotherapy on lung function is difficult to evaluate both in the shortand long-term. A recent Cochrane review investigating the benefit of physiotherapy in CF patients identified few randomised studies that evaluated the various physiotherapy methods; some studies showed positive short-term effects but none were able to show long-term effects [63].…”
Section: Exercise and Physiotherapymentioning
confidence: 99%
“…9 Manual techniques may be influenced by many situations, including physiotherapist experience, which may result in variability of the technique. The reproducibility of physiotherapy maneuvers has been described previously, and its variability depends on the technique and the level of training of the professional applying it.…”
Section: Introductionmentioning
confidence: 99%